Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA): Grievance Mechanism - Alliance of Bioversity International and CIAT (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This Grievance Mechanism (GM) have been prepared to guide the receipt, management, and redress of complaints and questions from project affected persons and stakeholders of the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project. It outlines the principles and provides arrangement for receiving, resolving and managing complaints from the community through the in-country research institution up to the Program Management Unit. It offers multiple avenues for receiving complaints as well as the protocol for receiving and managing complaints from victims of SEA/SH in a safe, confidential, and non-stigmatizing manner. The overall implementation of the AICCRA project is being led and coordinated by the International Center for Tropical Agriculture (CIAT) with support from other CGIAR centers. Therefore, CIAT as the Lead Center has prepared this GM to fulfill its commitment on project safeguard requirements and conformity to good international practices on grievance management.